Guided inquiry learning model application to train students' critical thinking skills on chemical equilibrium material - Firda Faradila Sholikhah; Dian Novita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The purpose of this study is to analyze the effect of the application of the guided inquiry learning model on activities of students, the products of student learning, students' skills in critical thinking, and student reactions to chemical equilibrium material. The design of this study applies a one-group pretest-posttest design. Thirty students of the eleventh grade at Kemala Bhayangkari 1 Surabaya Senior High School were used as the subject of this study. The percentage of application of each phase of the guided inquiry learning model are meetings 1, 2, and 3 was 96.9%, 98.6, and 100%, respectively. Student activities support the application model with a percentage of the total relevant activities of 92.69%. Student learning outcomes on factors that affect the shift in the direction of chemical equilibrium with n-gain obtained a score of 80%, which is high in the category. The results of students' skills in critical thinking in every phase with a high n-gain score are 53.33% interpretation, 40% inference, 63.33% analysis, 60% explanation, and 80 % evaluation. The student responses have a very good category with 99.15%.